Evaluasi Tata Letak Bangunan terhadap Garis Sempadan Jalan di Kecamatan Tomoni, Kabupaten Luwu Timur - Hidayatullah, Moesayyid; Listyarini, Sri (LPPM Universitas Terbuka, 2023)
The Mangkutana, Tomoni, and Tomoni Timur Urban Areas, later shortened to “Matoto”, are urban areas in East Luwu Regency. The center of economic activity in this region is located in Tomoni District, which later experienced regional development. The development of the region has led to substantial building growth that does not comply with the Regional Regulation (Perda) of East Luwu Regency Number 5 of 2012, as amended by Regional Regulation Number 8 of 2018, concerning Border Lines. Therefore, we are interested in evaluating the layout of buildings in the sub-district that violate and do not conform to existing regional regulations. Next, we specify the research area on the Trans Sulawesi Road Section. This study aims to assess the extent of non-conformity of building lot areas with regional regulations. The analysis employed is overlay analysis with union commands. The results of the analysis indicate that the area of building lots that encroached into the Rumaja area was 46.76%, Rumija covering an area of 16.70%, and Ruwasja at 36.54%.